ANALISIS PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN IKLIM ORGANISASI TERHADAP KINERJA GURU SMK (Survei pada SMK Swasta di Kecamatan Sukoharjo) - Prananingsih, Retno (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2021)
The aim of this study is to determine the significant influence between: (1) Leadership style of the headmaster on the work performance of private Vocational school teacher in Sukoharjo sub-district, (2) Motivation on the work performance of private vocational school teacher in Sukoharjo sub-district and (3) the organizational climate on the work performance of private vocational school teacher in Sukoharjo sub-district. The population of this study is 80 teachers which is came from 25% of all private vocational school teachers in Sukoharjo sub-district. The analysis technique which is used in this study is multiple linear regression with the classical assumption test. The results of the analysis are (1) The questionnaire for leadership style, motivation, organizational climate and teacher work performance variables is valid. The results of the reliability test were reliable, (2) it also passed the multicollinearity test ,the heteroscedasticity test, the autocorrelation test, and the normality test. The results of the analysis shows that: leadership style and organizational climate have significant effect to the private vocational school teacher work performance in Sukoharjo sub-district, but motivation doesn’t have significant effect to the private vocational school teacher work performance in Sukoharjo sub-district. Keywords: leadership style, motivation, organizational climate and teacher work performance